2022
DOI: 10.2147/idr.s354934
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Four Groups of Chromosome-Borne Accessory Genetic Elements Carrying Drug Resistance Genes in Providencia

Abstract: Purpose The aim of this study was to gain a deeper genomics and bioinformatics understanding of diversification of accessory genetic elements (AGEs) in Providencia . Methods Herein, the complete genome sequences of five Providencia isolates from China were determined, and seven AGEs were identified from the chromosomes. Detailed genetic dissection and sequence comparison were applied to these seven AGEs, together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…On the other hand, we observed the parallel horizontal transfer of local bla NDM genetic environments (manifesting as intact Tn 125 and its various truncated derivatives) into the existing bla NDM -empty plasmids belonging to different Inc groups. In addition, our previous studies have reported the capture of local bla NDM genetic environments by the accessory genetic elements embedded within Providencia chromosomes [ 42 , 45 ]. The exogenous integration of intact Tn 125 is mostly likely due to transposon jumps, while that of its truncated derivatives should be driven by homologous recombination [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we observed the parallel horizontal transfer of local bla NDM genetic environments (manifesting as intact Tn 125 and its various truncated derivatives) into the existing bla NDM -empty plasmids belonging to different Inc groups. In addition, our previous studies have reported the capture of local bla NDM genetic environments by the accessory genetic elements embedded within Providencia chromosomes [ 42 , 45 ]. The exogenous integration of intact Tn 125 is mostly likely due to transposon jumps, while that of its truncated derivatives should be driven by homologous recombination [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…are usually isolated from patients with urinary tract infections and diarrhea and are associated with nosocomial outbreaks. Most commonly, P. rettgeri and P. stuartii represent the majority of MDR strains isolated and are intrinsically resistant to penicillins and the first-generation cephalosporins, aminoglycosides, tetracyclines (including tigecycline), and colistin [302,303].…”
Section: Other Enterobacteralesmentioning
confidence: 99%
“…A unit transposon carries a core transposition module to achieve horizontal gene transfer ( 14 ). Our previous studies ( 15 17 ) have shown genetic characteristics of novel transposons carrying bla IMP ( bla IMP-8 -carrying ICE Tn 6397 , bla IMP-38 -carrying unit transposon Tn 6382 , and bla IMP-1 -carrying unit transposon Tn 6910 ).…”
Section: Introductionmentioning
confidence: 99%